Reconstruction of Sentencing for Public Officials Committing Corruption Crimes Based on Restorative Governance in the Perspective of Ta‘zīr - Noor Azizah; Zulham Zulham (Universitas Islam Sultan Agung, 2026)
Public officials who commit corruption crimes constitute a systemic form of crime that has broad impacts on economic stability, public trust, and the effectiveness of governmental governance. Although the provisions under Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 have established strict sanctions, the predominantly retributive sentencing approach is considered insufficient to realize substantive justice, particularly in terms of state financial recovery and institutional reform. This study aims to reconstruct a sentencing model for public officials involved in corruption crimes based on Restorative Governance within the perspective of Ta‘zīr. The research employs a normative juridical method with statutory and conceptual approaches, alongside qualitative analysis of primary and secondary legal materials. The findings reveal that the Restorative Governance approach emphasizes the recovery of state losses, the strengthening of accountability, and governance system reforms, which are conceptually aligned with the principles of Ta‘zīr in Islamic criminal law that are flexible and oriented toward public benefit (maslahah). The novelty of this research lies in the integration of the concepts of Restorative Governance and Ta‘zīr in formulating a more adaptive and justice-oriented sentencing model for corruption crimes. This study recommends reforms in criminal law policy through strengthening restorative approaches within the sentencing system in order to enhance the effectiveness of combating corruption crimes.